Analysis of Frequency Distribution and Histogram of Inflation Rates in Indonesia for the Period 2020–2024 - Trigarcia Maleachi Randa; Loria Amisah Lubis (Ecoplan, 2026)
This study analyzes Indonesia’s monthly inflation rates from January 2020 to December 2024 using descriptive statistical methods, namely frequency distribution tables and histograms with trend lines. The results show that inflation during this five-year period predominantly remained within the low to moderate range of 1.00%–3.00%. The distribution is positively skewed, indicating that lower inflation values occurred more frequently, while higher inflation rates were relatively rare. The most frequent class interval was 1.00%–1.67%, accounting for 26.67% of the total observations, and nearly 70% of the data fell below 3.01%, reflecting relative price stability. However, temporary inflation spikes were observed between 2022 and early 2023, likely influenced by global supply chain disruptions and commodity price volatility. Overall, the findings suggest that Indonesia’s inflation remained largely controlled throughout the study period, highlighting the role of policy measures during and after the COVID-19 pandemic. This study demonstrates the effectiveness of simple descriptive statistical tools in identifying key characteristics and trends in macroeconomic data.